A case-control study on risk factors for falls among older adults attending Klinik Rawatan Keluarga in Hospital Universiti Sains Malaysia - Ling, Chow Pei (2016)
Background: Falls is an important geriatric problem due to its potential negative impacts on the affected older adults. But, little is known about the risk factors for falls among older adults who attend the health clinics. Objectives: The objective of the study was to identify the associated factors for falls among older adults attending Klinik Rawatan Keluarga (KRK) of Hospital Universiti Sains Malaysia (USM). Methods: An unmatched case- control study was conducted among 60 older adults with self- reported falls and 60 “normal controls”. Both cases and controls were recruited from the KRK, Hospital USM via convenient sampling from December 2014 to June 2015. All participants completed a questionnaire regarding sociodemographic and other health risk factors. Logistic regression analysis was used for obtaining the odds ratio (OR) for associated factors. Results: Independent associated factors observed for falls were female sex (adjusted OR: 5.72, 95% CI: 2.50, 13.07, p <0.001) and impaired physical function capacity (adjusted OR: 4.33, 95% CI: 1.67, 11.28, p = 0.003). vii Conclusions: Female older adults and older adults with impaired physical function capacity were significant associated factors for falls among older adults attending KRK, Hospital USM.